2004
DOI: 10.1111/j.1365-2141.2004.05098.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of neutrophil CD177 mRNA expression in Ph‐negative chronic myeloproliferative disorders

Abstract: Summary The PRV‐1 gene has been proposed as a marker of polycythaemia vera (PV). PRV‐1 and NB1 are alleles of the polymorphic gene CD177, which belongs to the Ly‐6/uPAR superfamily, and their coding regions differ at only four nucleotides. We studied neutrophil CD177 mRNA levels in normal subjects and in 235 patients with Ph‐negative chronic myeloproliferative disorders (CMD), including PV, essential thrombocythaemia and myelofibrosis with myeloid metaplasia. Additional disease states were investigated for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…2 In a study on 235 patients with Ph-negative chronic myeloproliferative disorders, we found increased neutrophil CD177 mRNA levels in PV patients, but concluded that neutrophil CD177 mRNA overexpression, rather than a specific marker of disease, is a marker of abnormal neutrophil production and/or release in PV patients. 3 Similar observations were made by other investigators. 4,5 Recent studies suggest that evaluation of neutrophil CD177 mRNA may be employed for evaluating response to treatment.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…2 In a study on 235 patients with Ph-negative chronic myeloproliferative disorders, we found increased neutrophil CD177 mRNA levels in PV patients, but concluded that neutrophil CD177 mRNA overexpression, rather than a specific marker of disease, is a marker of abnormal neutrophil production and/or release in PV patients. 3 Similar observations were made by other investigators. 4,5 Recent studies suggest that evaluation of neutrophil CD177 mRNA may be employed for evaluating response to treatment.…”
supporting
confidence: 80%
“…In fact, we previously found that neutrophils isolated from the bone marrow, or from peripheral blood following granulocyte colony-stimulating factor administration, show markedly higher CD177 expression than circulating granulocytes on steady state. 3 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The marker expression in patients with SE and healthy controls was comparable ( Figure 1B). We also examined the expression of PRV1 and NF-E2, 2 markers previously shown to be elevated in MPDs, 10,11,14,[16][17][18] and ANKRD15, a putative tumor suppressor gene located within the minimal 9pLOH region. 7,19 Consistent with the previous reports, 10,11,14,[16][17][18] PRV1 and NF-E2 exhibited elevated expression in PV, IMF, and ET, whereas ANKRD15 mRNA was decreased in PV and IMF ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…ET shares both bone marrow histological (dysmorphic megakaryocyte proliferation with clustering) and clinical (increased risk of thrombohaemorrhagic events) phenotype with PV (Michiels & Thiele, 2002;Elliott & Tefferi, 2005). Similarly, a substantial number of patients with ET display PV-characteristic biological features including clonal myelopoiesis (Fialkow et al, 1981), in vitro growth factor independence/hypersensitivity of both erythroid and megakaryocyte progenitor cells (Juvonen et al, 1993;Axelrad et al, 2000), low serum erythropoietin level (Messinezy et al, 2002), altered megakaryocyte/platelet Mpl expression (Harrison et al, 1999a;Yoon et al, 2000), increased neutrophil PRV-1 expression (Passamonti et al, 2004b;Tefferi et al, 2004a), and decreased platelet serotonin content (Koch et al, 2004). Furthermore, another shared molecular phenotype between ET, PV, and several other MPD has recently been reported and involves an activating JAK2 tyrosine kinase mutation (JAK2 V617F ) (Baxter et al, 2005;James et al, 2005; Summary Clinical correlates and long-term prognostic relevance of the JAK2 V617F mutation was studied in 150 patients with essential thrombocythaemia (ET) from a single institution and followed for a median of 11AE4 years.…”
mentioning
confidence: 99%